The impact of consumer boycott on corporate financial performance: Evidence from PT Unilever Indonesia TBK - Muhammad Astri Yulidar Abbas; Alisanabela Nasrun; Siti Rohmah; Rudy Syafariansyah Dachlan (International Journal of Applied Finance and Business Studies, 2026)
This study examines the comparative financial performance of PT Unilever Indonesia Tbk before and during the viral boycott of Israeli/pro-Israel products in Indonesia. Using a quantitative comparative approach, financial performance is evaluated through liquidity, solvency, activity, and profitability ratios based on quarterly financial reports from Q4-2022 to Q3-2024. The findings indicate fluctuations in several financial ratios during the boycott period; however, the overall financial performance category remained relatively stable. Liquidity and solvency ratios were categorized as suboptimal both before and during the boycott, while profitability and activity ratios largely remained in the optimal category.